Patient satisfaction in the S. João Health Center from 2002 to 2007 - Hespanhol, A (2008)
Aims: To know the overall satisfaction of São João Health Centers patients and their satisfaction with all the other aspects of the service provided by the Health Center. Methods:We used a self administered questionnaire to all the patients that went to São João Health Center during one week (18-22 June 2007). Results: The questionnaire was answered by 78% of the patients (n=359). All the variables of the overall satisfaction of São João Health Centers patients and their satisfaction with all the other aspects show high values of median, percentile 90 and percentile 10, with the exception of these aspects: 10% of the respondents is very much insatisfied with I am satisfied with the time that I spend to get an appointment of a consultation, I wait little time in this Health Center, since I arrive until I am attended and Its easy to travel to this Health Center». Conclusions: São João Health Centers patients show high levels of satisfaction with the health care delivered, with the exception of the waiting times. This quality problem must be selected to promote several Cycles of Quality Assurance integrated in a Program to establish a Quality Assurance process in São João Health Center.